Inspection Times and Optimal Censoring Scheme for Generalized InvertedExponential Distribution with Progressive type I Interval Censored Data - Al-Mosawi, Riyadh R.; Qader, Abdullah Abdul (Iraqi Journal of Science, 2024)
In this article, two issues related to the design of the experiment are investigated; namely the inspection times and optimal censoring. In the first issue, we study four different approaches to determine the inspection times, namely; pre-specified, equally spaced, optimally spaced, and equal probability using two optimality criteria. In the second issue, we identify the optimal censoring scheme by finding the expected numbers of removals or proportions that attain a specific optimality criterion using two optimality criteria considered. Numerical comparisons using the Monte Carlo simulations are provided of the inspection times, optimum control schemes issues for different parameters and different sample sizes. Statistical measures such as bias and root mean square error for both pre-specified and equal space methods are calculated and the inspection times for different values of the censoring percentage h are obtained.